Strategi Pengembangan Desa Madobag sebagai Desa Wisata Budaya di Kabupaten Kepulauan Mentawai - Zulhitra, Deki; Yuliana, Yuliana; Pasaribu, Pasaribu (Journal of Home Economics and Tourism, 2016)
The aim of this research was to describe the development strategy (strength, weaknesses, opportunities, treats) in Madobag Village as a Cultural Tourism Village in Mentawai Island Regency. The type of this research was descriptive with qualitative data. Technique of data collection was done by using interviews, observations, and documentation methods. This research used a Snowball Sampling technique involving informants in it, they were: two people of cultural field (Tourism Government Service), and five local people of Madobag Village. Results of research can be done for developing a Madobag village as a Cultural Tourism Village in the Mentawai Islands are as follows: 1). Provide attractions like social gatherings or society together indigenous Mentawai. 2). Collaborates with a travel agent to make a cultural tour packages as a destination for these excursions. 3). Boost cooperation between village officials, local authorities and attract investors to develop the village Madobag as Cultural Tourism Village. 4). Highlighting the potential of cultural tourism village owned Madobag village by organizing cultural events.Keywords: Strategy, Development, Tourism Village.